Industrial Relations as a Discipline and Field in France and the UK - Almond, Philip (Relations industrielles / Industrial Relations, 2004)
This article analyses the differences in the post-war study of employment relations in the UK and France, examining both the orientations of the main literatures, and more recent developments in response to the changes of recent years. Through a comparison of the literature, the article seeks to analyse the implicit assumptions behind research in the field. The predominant means of investigating employment relations in both countries are seen to have been over-fixed on normative assumptions drawn from the specific circumstances of the post-war industrial relations climates of the two countries. This provides a partial explanation for the emergence of new normative frameworks, including that of Human Resource Management, particularly in the UK It is argued that in order for a move away from an explicitly managerial agenda to occur, researchers into industrial relations, particularly in English-speaking countries, must integrate their arguments within a greater awareness of wider societal change.